2021
DOI: 10.3389/fgene.2021.625867
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Strip1 Expression in Mouse Cochlear Hair Cells

Abstract: Striatin-interacting protein 1 (Strip1) is a core component of the striatin interacting phosphatase and kinase (STRIPAK) complex, which is involved in embryogenesis and development, circadian rhythms, type 2 diabetes, and cancer progression. However, the expression and role of Strip1 in the mammalian cochlea remains unclear. Here we studied the expression and function of Strip1 in the mouse cochlea by using Strip1 knockout mice. We first found that the mRNA and protein expression of Strip1 increases as mice ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…While supporting cells function as potential resources to regenerate HCs after damage (Lu et al, 2017;Zhang et al, 2017;Tan et al, 2019;Zhang S. et al, 2019Chen et al, 2021). Sensorineural hearing loss has many etiologies, varying from genetic defects (Zhu et al, 2018;Fang et al, 2019;Yang et al, 2019;Qian et al, 2020;Cheng et al, 2021;Fu et al, 2021a;Lv et al, 2021;Zhang et al, 2021) to environmental factors, including aging (Zhang et al, 2017;Fu et al, 2018;Li H. et al, 2018;He et al, 2020He et al, , 2021, noise and ototoxic drugs (Liu et al, 2016;He et al, 2017;Gao et al, 2020;Zhong et al, 2020;Fu et al, 2021b). TSAN is a rare phenotype with high clinical heterogeneity, manifesting as transient bilateral HL due to an increase in the core body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…While supporting cells function as potential resources to regenerate HCs after damage (Lu et al, 2017;Zhang et al, 2017;Tan et al, 2019;Zhang S. et al, 2019Chen et al, 2021). Sensorineural hearing loss has many etiologies, varying from genetic defects (Zhu et al, 2018;Fang et al, 2019;Yang et al, 2019;Qian et al, 2020;Cheng et al, 2021;Fu et al, 2021a;Lv et al, 2021;Zhang et al, 2021) to environmental factors, including aging (Zhang et al, 2017;Fu et al, 2018;Li H. et al, 2018;He et al, 2020He et al, , 2021, noise and ototoxic drugs (Liu et al, 2016;He et al, 2017;Gao et al, 2020;Zhong et al, 2020;Fu et al, 2021b). TSAN is a rare phenotype with high clinical heterogeneity, manifesting as transient bilateral HL due to an increase in the core body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Sound is collected and conducted by external and middle ear, then transformed into the electric signals by cochlear hair cells ( Wang et al, 2017 ; Liu Y. et al, 2019 ; Qi et al, 2019 , 2020 ; Zhang Y. et al, 2020 ); while spiral ganglion neurons is function as the neural auditory transduction cells ( Sun et al, 2016 ; Guo et al, 2019 , 2021 ; Liu W. et al, 2019 ; Zhao et al, 2019 ). The cochlear hair cells are sensitive to aging, acoustic trauma, ototoxic drugs, and environmental or genetic influences ( O’Donnell et al, 1988 ; Zhu et al, 2018 ; Fang et al, 2019 ; Jiang et al, 2020 ; Qian et al, 2020 ; Lv et al, 2021 ; Zhang et al, 2021 ). Previous studies have shown that oxidative stress and cell apoptosis play important roles in hair cell loss ( Sun et al, 2014 ; Yu et al, 2017 ; Li et al, 2018 ; Gao et al, 2019 ; Zhang Y. et al, 2019 ; Zhang et al, 2020b ; Zhong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cochlear hair cells are sensitive to aging, acoustic trauma, ototoxic drugs, and environmental or genetic influences ( Zhu et al, 2018 ; Fang et al, 2019 ; He et al, 2020 ; Jiang et al, 2020 ; Qian et al, 2020 ; Lv et al, 2021 ; Zhang et al, 2021 ). Previous reports have shown that oxidative stress and cell apoptosis play important roles in noise induced hair cell loss and ribbon synaptopathy ( Sun et al, 2014 ; Yu et al, 2017 ; Li et al, 2018 ; Gao et al, 2019 ; He et al, 2019 ; Zhang Y. et al, 2019 ; Zhong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%